Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2020)
A dataset containing 399009 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Elymus repens (L.) Gould" ] } The dataset includes 399009 records from 852 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0075885-200221144449610/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences